Da'wah and Transformative Leadership: Tuan Imam's Role in Nurturing Islamic Values in Kampung Kasih Sayang - Jamaludin, Jamaludin; Junaidi, Junaidi; Nurainun, Nurainun; Pratama, Muhammad Yoga; Harahap, Nurul Febriyani (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
Originating from the nickname